Factors associated with timely receipt of COVID vaccination in patients with cancer. Issue 28 (1st October 2022) - Powis, Melanie Lynn; Sutradhar, Rinku; Patrikar, Aditi; Cheung, Matthew; Gong, Inna Y.; Vijenthira, Abi; Hicks, Lisa K.; Wilton, Drew; Krzyzanowska, Monika K.; Singh, Simron
Abstract : 167 Background: In many jurisdictions patients with new hematological cancers, or those receiving hematopoietic stem cell transplant or immunosuppressive agents, were prioritized for COVID vaccination due to increased risk of infection and death. In Ontario, Canada those residing in congregate settings, or regions with high positivity rates or high proportions of essential workers were also prioritized. While vaccine inequities exist, it remains unclear whether they persisted amongst the prioritized cancer population. Methods: We undertook a retrospective, population-based study to evaluate factors associated with COVID vaccination in patients residing in Ontario, Canada, >18 years of age, and diagnosed with cancer between 01/2010 and 09/2020. Factors associated with time from vaccine approval to full vaccination (two doses) and third doses were evaluated using multivariable Cox proportional hazards regression models. Results: The cohort consisted of 356, 535 patients; as of 30 January 2022 of which 86.8% had received at least two doses. Compared to patients with more remote diagnoses (> 1 year), newly diagnosed patients rate of vaccination was lower (HR: 0.89, 95%CI: 0.88-0.91, p < 0.01) and a greater proportion were unvaccinated (13.6% vs 11.8%; p < 0.01). Conversely, rate of vaccination was higher in patients treated with systemic therapy in the last 6 months (HR: 1.04, 95%CI: 1.03-1.05, p < 0.01). Rate of vaccination was 25% lower in recent (HR:0.74, 95% CI: 0.72-0.76, p < 0.01) and non-recent immigrants (HR: 0.80, 95% CI: 0.79-0.81, p < 0.01), and a greater proportion remained unvaccinated, compared to those who were Canadian-born (20.1 and 16.6% vs 10.9%; p < 0.01). Compared to the most advantaged quintiles, quintiles with the lowest socioeconomic status (14.5% vs 9.4%; p < 0.01), or highest residential instability (13.3% vs 10.8%; p < 0.01), material deprivation (10.5% vs 9.6%; p < 0.01), or ethnic concentration quintiles (13.7% vs 10.4%; p < 0.01) had higher proportions of unvaccinated patients. Rate of vaccination was 20% lower in patients with the lowest socioeconomic status (HR: 0.83, 95% CI: 0.81-0.84, p < 0.01) and those with highest material deprivation (HR: 0.80, 95% CI: 0.79-0.82, p < 0.01) relative to more advantaged groups. Similar trends were observed for receipt of third doses in the eligible cohort. Conclusions: Despite direct government funding of COVID vaccines and distribution policies aimed a prioritizing high-risk populations marginalized patients with cancer were less likely to be vaccinated than other cancer patients. Differences in receipt of vaccination are likely due to the interplay between systemic barriers to access (low trust, transportation barriers, work schedules), and cultural/ social influences impacting uptake. Future efforts should work directly members of high-risk communities to understand how to improve vaccine delivery among these communities.